Novel hollow mesoporous 1D TiO2 nanofibers as photovoltaic and photocatalytic materials - Mhaisalkar, Subodh Gautam (2012)
Hollow mesoporous one dimensional (1D) TiO2 nanofibers are successfully prepared by co-axial electrospinning of a titanium tetraisopropoxide (TTIP) solution with two immiscible polymers; polyethylene oxide (PEO) and polyvinylpyrrolidone (PVP) using a core–shell spinneret, followed by annealing at 450 °C. The annealed mesoporous TiO2 nanofibers are found to having a hollow structure with an average diameter of 130 nm. Measurements using the Brunauer–Emmett–Teller (BET) method reveal that hollow mesoporous TiO2 nanofibers possess a high surface area of 118 m2 g−1 with two types of mesopores; 3.2 nm and 5.4 nm that resulted from gaseous removal of PEO and PVP respectively during annealing. With hollow mesoporous TiO2 nanofibers as the photoelectrode in dye sensitized solar cells (DSSC), the solar-to-current conversion efficiency (η) and short circuit current (Jsc) are measured as 5.6% and 10.38 mA cm−2 respectively, which are higher than those of DSSC made using regular TiO2 nanofibers under identical conditions (η = 4.2%, Jsc = 8.99 mA cm−2). The improvement in the conversion efficiency is mainly attributed to the higher surface area and mesoporous TiO2 nanostructure. It facilitates the adsorption of more dye molecules and also promotes the incident photon to electron conversion. Hollow mesoporous TiO2 nanofibers with close packing of grains and crystals intergrown with each other demonstrate faster electron diffusion, and longer electron recombination time than regular TiO2 nanofibers as well as P25 nanoparticles. The surface effect of hollow mesoporous TiO2 nanofibers as a photocatalyst for the degradation of rhodamine dye was also investigated. The kinetic study shows that the hollow mesoporous surface of the TiO2 nanofibers influenced its interactions with the dye, and resulted in an increased catalytic activity over P25 TiO2 nanocatalysts.